2004
DOI: 10.1038/sj.cgt.7700760
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant interleukin-12 gene therapy for the management of colorectal liver metastases

Abstract: In humans, no efficient treatment exists not only against multifocal liver metastases (LM) but also against recurrent microscopic liver metastases within the liver remnant following curative liver resection. Furthermore, in nonmultifocal LM, partial liver resection could be performed, but in more than 50% of the patients, tumor recurrence within liver remnant is observed, partly due to the growth of dormant cancer cells in the setting of postoperative host immune dysfunction. We investigated the therapeutic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…We believed that this model might modify the host immune antitumoral response and is too far from the clinical situation. We recently developed another model with partial hepatectomy after intraportal injection of cancer cells within all of the lobes of the liver [14]. In the present study, we demonstrated that this model was not only feasible and reproducible, but also mimicked quite well what is observed in humans: no macroscopic tumors within the remnant liver at the time of partial hepatectomy but evidence of tumors 27 days later.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We believed that this model might modify the host immune antitumoral response and is too far from the clinical situation. We recently developed another model with partial hepatectomy after intraportal injection of cancer cells within all of the lobes of the liver [14]. In the present study, we demonstrated that this model was not only feasible and reproducible, but also mimicked quite well what is observed in humans: no macroscopic tumors within the remnant liver at the time of partial hepatectomy but evidence of tumors 27 days later.…”
Section: Discussionsupporting
confidence: 78%
“…Not only a direct cytotoxic effect by HSV1-TK gene transfer and Ganciclovir treatment was noted but also an induction of activated T cells leading to an antitumoral efficiency, called "bystander effect" [5]. In a recent study, we showed in a model of nonresectable liver metastases that retroviral vectors expressing IL-12 gene significantly reduced tumor volume because the combination of IL-12 and HSV1-TK gene transfer was more effective than therapy with either of the two vectors alone [14]. However, in this study [14], as well as in other reports, because the rate of transfected cancer cells remains low after in vivo gene transfer, it could represent a limitation for either curative or preventive treatment in humans.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has profound antitumor efficacy that was demonstrated on a variety of different types of tumors and metastases in preclinical as well as clinical studies. In recent years, several excellent reviews describing the activities of IL-12, the preclinical and clinical use of recombi-nant IL-12 and gene therapy with IL-12 have been published [1,8,11,45,56,57]. On the other hand, 10 years have passed since the first paper on combination of plasmid DNA encoding for IL-12 injected intramuscularly with electroporation was published [39].…”
Section: Introductionmentioning
confidence: 99%
“…The delivery systems for IL-12 gene therapy are various and include transfer of naked plasmid DNA alone [27,28], adenoviral [29][30][31][32][33] or other viral vectors [34][35][36], as well as gene gun [37,38], electroporation [39][40][41][42] and other non-viral vectors [43,44]. Clinical studies in human and also in veterinary oncology were initiated and the first results showed that IL-12 gene therapy is a safe treatment with some beneficial clinical effect [28,[45][46][47][48][49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%